Improving the Ability to Read Yellow Book Among Students in the Da'wah Management Program and Congregational of the Nurul Hidayah Mosque, Manado - Ali Ridho; Rusdiyanto; Sahari; Muhammad Imran; Mardan Umar; Zainun Nur Hisyam Tahrus (Universitas Syiah Kuala, 2026)
The poor ability to read classical Islamic texts among students at state Islamic universities and among the Muslim community indicates that their level of religious literacy is also low. Therefore, a training program on reading the classical Islamic text Nashaihul Ibad is needed for students in the Da'wah Management Program at IAIN Manado and the congregation of the Nurul Hidayah Mosque in Manado City. This study employs a descriptive qualitative method of an analytical nature and aims to identify the steps implemented to improve the ability of students and mosque congregants to read classical Islamic texts. Primary data were obtained through interviews, observations, and documentation. Secondary data were derived from books and scholarly articles published in reputable journals. The study concluded that the classical Islamic texts reading program was conducted over one semester, consisting of eight sessions. Each session had specific discussion topics, and the methods applied were blandongan and sorogan. The obstacles identified included a low mastery of Arabic grammar (nahwu) and morphology (sharaf), weak intention and motivation, an educational background not from an Islamic boarding school, an unsupportive environment, and limited study time.